The essential guide to lithium treatment - Bauer, Michael; Gitlin, Michael J. (Springer, 2016)
This book is a practical, up-to-date guide to the correct use of lithium for the short- and long-term treatment of mood disorders. Among the subjects addressed are the pharmacology and mechanisms of action of lithium, its use for maintenance treatment, the role of lithium in the treatment of mania and depression and in suicide prevention, further clinical indications, the administration of lithium during pregnancy and the postpartum period, and adverse effects and their management. Relevant background information is provided on the diagnosis, classification, and natural course of mood disorders, and an overview of other treatments for bipolar disorder and major depression is included. Lithium is the essential medication for patients with mood disorders. The evidence of its efficacy in maintenance treatment is acknowledged in all major international treatment guidelines for bipolar disorders and, when used correctly, lithium unquestionably produces the most dramatic benefits of any medication in psychopharmacology. This essential guide is written by two international experts in the treatment of mood disorders who have more than 25 years of experience in the use of lithium and have authored numerous scientific articles on lithium.